A Study on Legal and Ethical Dimensions of Healthcare Waste Disposal in Post Pandemic Era - Ms. Shweta Chaturvedi and Dr. Anjula Chowbe (Cuestiones de Fisioterapia, 2025)
The COVID-19 pandemic has had a significant influence on the worldwide healthcare sector, leading to anincrease in the output of healthcare waste. In order to maintain ethical and legal standards, safeguard publichealth, and avoid environmental damage, healthcare waste must be disposed of properly. Examining the potentialand problems that have arisen in the wake of the crisis, this paper explores the legal and ethical aspects ofhealthcare waste disposal in the post-pandemic era. By combining legal analysis with ethical considerations, thestudy adopts a multidisciplinary approach to tackling the difficulties associated with hospital waste management.The existing international, national, and local legal frameworks are examined, with a focus on the evolvingregulations and policies established in response to the pandemic.